DETECTION OF FINANCIAL STATEMENT FRAUD IN BANKS LISTED ON THE IDX USING THE BENEISH M-SCORE METHOD FOR THE YEARS 2023 AND 2024 - Astia Putriana; Anto Andreawan; Rahmatullah Alfikri; Rahmi Nadiar (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
This research aims to detect financial statement fraud in banking companies listed on the Indonesia Stock Exchange for the years 2022 and 2024 using the Beneish M-Score method. The data used in this study consists of financial statements from banking companies listed on the Indonesia Stock Exchange for the years 2023 and 2024. The data analysis technique is descriptive, employing the Beneish M-Score method, which includes 8 financial ratios: Days Sales In Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales General and Administrative Expenses Index (SGAI), Leverage Index (LVGI), and Total Accruals to Total Assets (TATA). The results of this study indicate that out of 47 banking companies listed on the Indonesia Stock Exchange for the years 2023 and 2024, 33 companies, or 70.21%, are classified as non-manipulators, while 14 companies, or 29.79%, are classified as manipulators. The banking companies most frequently indicated to manipulate financial statements are related to their accruals (TATA). The banking company suspected of having the highest level of manipulation is Bank Jtrust Indonesia Tbk. (BCIC). The banking company suspected of not indicating any financial statement manipulation is Bank Artha Graha Internasional Tbk. (INVC).